Frontispiece: Exosome therapeutics for COVID‐19 and respiratory viruses (View 3/2021). Issue 3 (17th June 2021) - Popowski, Kristen D.; Dinh, Phuong‐Uyen C.; George, Arianna; Lutz, Halle; Cheng, Ke
Abstract : In article number 20200186, Ke Cheng, Phuong‐Uyen C. Dinh, Kristen Popowski and their co‐workers describe the relationship between nanoparticles and respiratory viruses, to emphasize the clinical translation of exosome therapeutics for diseases such as SARS‐CoV‐2 infection. A naturally occurring extracellular vesicle, exosomes utilize similar endosomal sorting pathways and uptake mechanisms as viruses. In this cover, the gears represent the parallels between nanoparticle and viral mechanisms within the lung and how these biological systems can be utilized to enhance drug delivery and efficacy.